Differentiated Instruction Strategies to Enhance Reading Comprehension in Elementary Schools: A Systematic Literature Review - Astutik, Eva Yuli; Muhimmah, Hitta Alfi; Istiq’faroh, Nurul (Jurnal Paedagogy, 2026)
This study aims to identify evidence-based differentiated instruction (DI) strategies that enhance reading comprehension in elementary education. The research employed a systematic literature review following the PRISMA guidelines. A total of 16 empirical studies published between 2020 and 2025 were retrieved from the Scopus database based on their relevance and methodological rigor. The data were analyzed using qualitative thematic analysis and cross-study comparison to identify effective strategies and patterns of implementation. The findings indicate that differentiated instruction consistently improves reading comprehension outcomes, with reported gains ranging from 10% to 44%. Effective strategies include tiered instruction, flexible grouping, content–process–product differentiation, and technology-supported approaches. Instructional models such as identification–reflection–improvement cycles and Cooperative Integrated Reading and Composition (CIRC) demonstrated particularly strong effectiveness. Successful implementation was associated with continuous assessment practices, teacher preparedness, and access to differentiated instructional resources. In conclusion, this review confirms that differentiated instruction provides an effective framework for addressing diverse learner needs and improving reading comprehension outcomes in elementary classrooms.